Konseling Teknik Motivational Interviewing di MAN 4 Bantul Yogyakarta: Upaya Untuk Menguatkan Aktualisasi Diri Siswa - Abi Apriyadi (Counselle| Journal of Islamic Guidance and Counseling, 2022)
Abstract This study was conducted with the aim of determining the implementation of counseling motivational interviewing techniques provided by counseling guidance teachers to students who have problems with self-actualization that are not appropriate in acting or behaving in accordance with the demands of school conditions, as well as students who actualize themselves do not show proper student requirements in the school environment. In addition, the purpose of this research is to provide an overview of counseling motivational interviewing techniques provided by counseling guidance teachers in helping and motivating students to change their self-actualization to better self-actualization. This research method uses a qualitative approach to produce descriptive through the method of collecting data on interviews, observations, and documentation. The subjects in this study were counseling guidance teachers of MAN 4 Bantul Yogyakarta. For data analysis, this research goes through four processes, namely, data collection, data reduction, data presentation, and drawing conclusions. The results of this study show that counseling through motivational interviewing techniques is an effective counseling technique approach used to strengthen students' self-actualization. After being given motivational interviewing counseling, students can feel the changes in themselves and students are able to actualize themselves for the better in accordance with the conditions of the MAN 4 Bantul Yogyakarta students. Abstrak Penelitian ini dilakukan dengan tujuan untuk mengetahui implementasi konseling teknik motivational interviewing yang diberikan oleh guru bimbingan konseling kepada siswa yang memiliki permasalahan aktualisasi diri yang kurang tepat dalam bertindak maupun berperilaku yang tidak sesuai dengan tuntutan kondisi sekolah, serta siswa yang mengaktualisasikan dirinya tidak menunjukkan semestinya keharusan siswa di lingkungan sekolah. Selain itu juga, tujuan penelitan ini untuk memberikan gambaran konseling teknik motivational interviewing yang diberikan guru bimbingan konseling dalam membantu dan memotivasi siswa agar dapat merubah aktualsisasi diri mereka kepada pengaktualisasian diri yang lebih baik. Metode penelitian ini menggunakan pendekatan kualitatif guna menghasilkan secara deskriptif dengan melalui metode pengumpulan data wawancara, observasi, dan dokumentasi. Subyek dalam penelitian ini adalah guru bimbingan konseling MAN 4 Bantul Yogyakarta. Untuk analisis data penelitian ini melalui empat proses yakni, pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian ini menunjukkan bahwa konseling melalui teknik motivational interviewing merupakan suatu pendekatan teknik konseling yang efektif digunakan untuk menguatkan aktualisasi diri siswa. Setelah diberikan konseling motivational interviewing siswa dapat merasakan perubahan pada dirinya dan siswa mampu mengaktualisasikan dirinya menjadi lebih baik yang sesuai dengan kondisi seharusnya siswa MAN 4 Bantul Yogyakarta.